Analisis Tata Letak Fasilitas Produksi UMKM PCB XYZ Menggunakan Metode Activity Relationship Chart - Virda Hersy Lutviana Saputri; Raden Aryo Putra Pratama; Septian Yoga Dwi Cahyo; Mochammad Faiz Firdous; Felix Juan Rama; Arini Sekar Arum (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2026)
Productivity depends on determining the layout of facilities because if the layout is not paid attention to it can cause work to be hampered. Layout is a crucial factor for a company to design production facilities so as not to disrupt production activities. PCB XYZ is one of the MSMEs engaged in PCB manufacturing services in Yogyakarta. XYZ PCB plays a vital role in meeting the demand for high-quality PCBs for various technology applications. The placement of production facilities at XYZ PCB MSMEs is not well organized, resulting in slow processing times, and disrupting work productivity and effectiveness. This research aims to redesign the layout of the XYZ PCB factory. The methods used are Activity Relationship Chart (ARC), Activity Relationship Diagram (ARD), and Total Closeness Rating (TCR). ARC is used to analyze the relationship between one part and another regarding the proximity value. ARD to further analyze the linkages between departments. TCR to find out priority facilities that need to be considered when preparing the proposed layout. The results of this research show that the Assembly facility is a production priority with a TCR score of 27, which will receive workflow from the Machining, Programming, 3D Printing, and Component storage facilities which function to prepare components to be assembled. The Quality Control facility will test the results of the equipment from the assembly site. The Packing Facility is the end of the production process which will prepare the equipment delivery process by obtaining delivery information from the Office.